2010
DOI: 10.1038/ismej.2010.5
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of microbial communities colonising the hyphal surfaces of arbuscular mycorrhizal fungi

Abstract: Arbuscular mycorrhizal fungi (AMF) are symbiotic soil fungi that are intimately associated with the roots of the majority of land plants. They colonise the interior of the roots and the hyphae extend into the soil. It is well known that bacterial colonisation of the rhizosphere can be crucial for many pathogenic as well as symbiotic plant-microbe interactions. However, although bacteria colonising the extraradical AMF hyphae (the hyphosphere) might be equally important for AMF symbiosis, little is known regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
160
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(170 citation statements)
references
References 50 publications
7
160
1
2
Order By: Relevance
“…We assume that the highly enriched spot represents bacterial cells bound to the fungal hypha. Such strong association of bacterial cells to the hyphal surface was shown before (Artursson et al, 2006;Scheublin et al, 2010;Worrich et al, 2017). As the turnover rate of bacteria is generally considered to be higher compared to fungi (Rousk and Bååth, 2011), the bacteria or group of bacteria might have been transferred to the fungal hypha.…”
Section: Fungal Hyphae In the Rhizospherementioning
confidence: 99%
“…We assume that the highly enriched spot represents bacterial cells bound to the fungal hypha. Such strong association of bacterial cells to the hyphal surface was shown before (Artursson et al, 2006;Scheublin et al, 2010;Worrich et al, 2017). As the turnover rate of bacteria is generally considered to be higher compared to fungi (Rousk and Bååth, 2011), the bacteria or group of bacteria might have been transferred to the fungal hypha.…”
Section: Fungal Hyphae In the Rhizospherementioning
confidence: 99%
“…Several studies also show that AMF influence bacterial communities inhabiting the rhizosphere and mycorrhizosphere (Ames et al, 1984;Scheublin et al, 2010), including shifts in denitrifying communities (Amora-Lazcano et al, 1998;Veresoglou et al, 2012b). AMF influence the N cycle and can take up significant amounts of nitrogen (Hodge and Fitter, 2010;Veresoglou et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that the bacterial and fungal community structures in the roots of symbiosis-defective mutants of Medicago truncatula (32) and soybean (22) differ from those in the roots of wild-type host plants; it was also shown that certain microbes preferentially associate with arbuscular mycorrhizal roots (41) and nodulated (Nod ϩ ) roots (22). However, unexpectedly, analyses of the rhizosphere community in soybeans have revealed that the bacterial community in nonnodulated soybeans is more similar to that in hypernodulated soybeans than to that in wild-type soybeans (22).…”
mentioning
confidence: 99%